Characteristics of infertile couples attending OPD of a teaching hospital - Sinha, Parul; Pandey, Kiran; Srivastava, Anand; Chowdhary, Iti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is defined as failure to conceive even after one year of regular, frequent and unprotected intercourse. Infertility has, in the last few years surfaced in society as a significant problem affecting as many as 15% of couples. This study aimed at identifying the characteristics of infertility among Indian couples. Methods: The present study was carried out on 100 infertile couples attending the OPD of upper India sugar exchange maternity hospital attached to GSVM medical college, Kanpur, other hospital and nursing homes of Kanpur. Both the partners were completely evaluated by taking proper history, examination and investigation to assess the cause of infertility. Results: Majority of female partners were between ages of 25-29. Female factors were found in 45% couples and male factors in 30 % couples. Among female factors, tuboperitoneal factor was found in 32% cases and ovulatory factor was found in 40% cases. Oligospermia was the commonest cause in male factor infertility. Conclusions: From this study we concluded that infertility is a public health problem in India and the main infertility pattern is a primary rather than secondary infertility.